DNA barcoding and an updated key to the genus Hesperentomon (Protura: Acerentomata: Hesperentomidae), with a new species from Northwest China - Qian, Chang-Yuan; Bu, Yun; Luan, Yun-Xia (Zootaxa, 2018)
Hesperentomon bolense sp. n., described from Northwest China, is distinguished from other Hesperentomon spp. by having foretarsal sensillum b clearly shorter than c, a robust sensillum c broader than the other foretarsal sensilla, 18 posterior setae on the mesonotum and 16 posterior setae on the metanotum, 12 posterior setae on urotergites II–VI (P1a and P2a absent), 8 posterior setae on urosternites IV–VI (Pc absent), and absence of seta P2a on urotergite VII. The morphological characters of all described species of Hesperentomon are compared, and an updated identification key to species is given. The DNA barcodes of H. bolense sp. n. were compared to similar species of the genus; the K2P genetic divergences were 0–5.1% between individuals of H. bolense sp. n., but 21.4%–27.3% between H. bolense sp. n. and other congeneric species. The molecular data further confirmed H. bolense as a distinct species.